Inhibition of Influenza A Virus Replication by TRIM14 via Its Multifaceted Protein–Protein Interaction With NP - Wu, Xiangwei; Wang, Jingfeng; Wang, Shanshan; Wu, Fei; Chen, Zhigao; Li, Chunfeng; Cheng, Genhong; Qin, F. Xiao-Feng (Frontiers in Microbiology, 2019)
Influenza A virus (IAV) is a worldwide ongoing health threat causing diseases in both humans and animals. The interaction between influenza A virus and host is a dynamic and evolving process that influences the pathogenicity and host specificity of the virus. TRIM14, a member of tripartite motif (TRIM) family, has been demonstrated to possess a strong capability of regulating type І interferon and NF-κB induction in host defense against viral infection. In this study, we found that TRIM14 could restrict the replication of IAV in a type І interferon and NF-κB independent manner. Mechanistically, different domains of TRIM14 could selectively interact with the viral nucleoprotein (NP), resulting in disparate influences on the RNP formation and viral replication. In particular, the PRYSPRY domain of TRIM14 exhibited a potent inhibitory activity on NP protein stability and IAV replication. On the contrary, the ΔS2 domain could rather antagonize the function of PRYSPRY domain and promote the IAV RNP formation by stabilizing NP. At the biochemical level, TRIM14-NP interaction could induce the K48-linked ubiquitination and proteasomal degradation of NP. Moreover, due to the rapid degradation of newly synthesized NP, TRIM14 could effectively block the translocation of NP from cytoplasm to nucleus thus further restrain the propagation of IAV in host cells. Taken together, our study has unraveled a previously unknown mechanism of TRIM14 mediated inhibition on RNP formation and influenza virus replication, and provides a new paradigm of complex and multifaceted host-pathogen interaction between ISG and viral protein.